Analisis Kinerja Konsultan Pengawas Dalam Pelaksanaan Proyek Konstruksi - Dwiretnani, Annisaa; Dony, Wari; Manalu, Febry Arianto (Universitas Batanghari, 2024)
A civil construction project is said to be successful if it meets three parameters, namely cost, quality and time, where the project costs are in accordance with the budget, the quality of the project is achieved according to specifications or requirements and the maximum project duration is the same as the planned time. However, in its implementation, projects are often faced with certain conflicts, one of which has an impact on the completion time, so it is felt necessary to involve a supervisory consultant in it in the hope of being able to provide supervision and control over each work item's progress. In relation to roads as an example of a civil building in the form of land transportation infrastructure which includes all its parts, this is reflected in the Short Road Reconstruction Project - Tanah Garo in Muara Tabir District, Tebo Regency, Jambi Province which uses the 2022 National Economic Recovery Loan (PEN) funds amounting to Rp. . 49,638,999,000 for flexible pavement work along 13,503 m for 105 calendar days, research was carried out on several factors and variables regarding the significant role of supervisory consultants in keeping the project on track. The research method is qualitative analysis which is developmental in nature and uses the help of the Microsoft Excel 2019 application in processing data. From the results of the analysis, it was concluded that the performance of supervision and quality control of work carried out by CV. Atifa Cipta Plan as the supervisory consultant for the Short Road Reconstruction Project - Tanah Garo received the highest average score among the six other factors, namely 4.80, which means very good.